2019
DOI: 10.3819/ccbr.2019.140003
|View full text |Cite
|
Sign up to set email alerts
|

Meliorating the Suboptimal-Choice Argument

Abstract: Zentall's (2019) target article, "What suboptimal choice tells us about the control of behavior," is in three parts. The first part reviews a set of studies that have yielded surprising findings: In relatively simple choice tasks, animals seem to behave irrationally by making suboptimal choices. The second part introduces a set of hypotheses to account for the surprising findings: Animals may behave according to a variety of heuristics that are adaptive in their natural environments but maladaptive in the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…We have suggested that some errors occur because the pigeons have difficulty remembering the previously chosen stimulus and, importantly, the consequence of that choice (Smith, Beckmann, & Zentall, 2017). But Carvalho et al (2019) question that account because the pigeons rarely make errors during many of the early and late trials in the session, so memory cannot be a factor on those trials. Of course, there is no need to remember the last chosen stimulus and the outcome of that choice early and late in the session because, after many sessions of training, the appropriate early and late choices would be well established in reference memory.…”
Section: The Midsession Reversal Taskmentioning
confidence: 97%
See 4 more Smart Citations
“…We have suggested that some errors occur because the pigeons have difficulty remembering the previously chosen stimulus and, importantly, the consequence of that choice (Smith, Beckmann, & Zentall, 2017). But Carvalho et al (2019) question that account because the pigeons rarely make errors during many of the early and late trials in the session, so memory cannot be a factor on those trials. Of course, there is no need to remember the last chosen stimulus and the outcome of that choice early and late in the session because, after many sessions of training, the appropriate early and late choices would be well established in reference memory.…”
Section: The Midsession Reversal Taskmentioning
confidence: 97%
“…But it does not explain the results with pigeons involving two different kinds of grain, both intact (Zentall et al, 2014), or the finding with dogs involving a piece of carrot and piece of cheese (Pattison & Zentall, 2014), or even the results with monkeys involving a slice of cucumber and grape (Kralik, Xu, Knight, Khan, & Levine, 2012). Carvalho et al (2019) would also like an explanation for the individual differences. Given the fact that pigeons that showed the less is better effect were only minimally deprived of food, some of the individual differences may result from motivational differences.…”
mentioning
confidence: 94%
See 3 more Smart Citations